Penggunaan Strategi Digital dalam Layanan Kesehatan Rumah Sakit - Ni Luh Citra Mutiarahati; I Wayan Septa Wijaya; Ni Putu Indah Rosita (Indonesian Journal of Health Research, 2022)
Introduction: Digital technology used in hospitals has increased amount 50% to reach health care consumers, which is marked by the increasing demand for health care through applications. This study aims to determine digital strategies used in hospital health services. Methods: Research method used literature review study. Search literature in this literature review using databases in the form of Google Scholar and Pub Med. The prioritized articles revolve around the last 5 (five) years of research, but if there is a science or discussion that has not changed, it will be expanded to an article with the last 10 years of research. Journals were reviewed to select journals of measurement results that were appropriate to the topic from 2018 to 2022. The data used in this study were secondary data. Results: The results of the study show that the use of digital strategies has a tremendous impact, namely increasing more consumers through engagement on social media. Digital marketing in hospitals during this pandemic is a marketing strategy that has many benefits, which can attract new patients, expand business, increase customer/patient trust, strengthen customer/patient loyalty, increase brand awareness, encourage patients to use home services. sick and promote it to other patients and families.